2009
DOI: 10.1302/0301-620x.91b3.21274
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of treatment for dislocation after primary total hip replacement

Abstract: We have studied the natural history of a first episode of dislocation after primary total hip replacement (THR) to clarify the incidence of recurrent dislocation, the need for subsequent revision and the quality of life of these patients. Over a six-year period, 99 patients (101 hips) presented with a first dislocation of a primary THR. A total of 61 hips (60.4%) had dislocated more than once. After a minimum follow-up of one year, seven patients had died. Of the remaining 94 hips (92 patients), 47 underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 35 publications
4
57
1
2
Order By: Relevance
“…Five patients had soft tissue destruction to the point where a portion or all of the hip abductor insertion required attempted repair. Patient outcome scores were found to be fair, regardless of the measurement tool used, and comparable to other studies for revision for pseudotumour 23 , MoM revision cases [24][25][26] , and revision for instability in MoP THR 21 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Five patients had soft tissue destruction to the point where a portion or all of the hip abductor insertion required attempted repair. Patient outcome scores were found to be fair, regardless of the measurement tool used, and comparable to other studies for revision for pseudotumour 23 , MoM revision cases [24][25][26] , and revision for instability in MoP THR 21 .…”
Section: Discussionsupporting
confidence: 79%
“…The pattern of presentation in this series is consistent with this because the time from index surgery to revision was just under six years (mean 57 months). This contrasts with revision for early instability in MOP THR, which is usually required within 6 months of index surgery 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The constraining force of the ring is greater than 600 lbs for the 32-mm liner and 325 lbs for the 28-mm liner [50]. The leveraged torque to disengage the femoral head was 150 inch-lbs [30]. The cutouts are designed to reduce impingement in full flexion with internal rotation and in extension with external rotation as well as to maximize ROM.…”
Section: Appendix 1: Devices Examined In This Studymentioning
confidence: 99%
“…A landmark review in 1982 by Woo and Morrey of over 10 000 primary THAs reported a dislocation rate of 3.2% [1] . Other studies have reported dislocation rates of 0.3% to 10% for primary THAs and up to 28% for revision THAs [2][3][4][5][6][7][8][9][10][11][12][13][14] . The risk of dislocation is influenced by patient factors such as age, sex, previous surgery, and cognitive or neurologic disorders as well as surgical factors, including surgical approach, choice of implant, soft tissue and surgeon experience [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%